Challenges of Post-COVID-19 for a Sustainable Development Society (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The COVID-19 pandemic has causedenormous upheaval at the micro-, meso- and macrosocial levels, with a profound influence on the diverse dimensions of human existence. This reprint offers contributions by authors from various backgrounds and origins for a better understanding of the multiple and interdependent consequences of the COVID-19 pandemic that pose multiple and complex scientific, moral, social and political challenges, considered from social science perspectives.